The improvement of thin polymer film properties through plasma immersion ion implantation and deposition technique - Rangel, Elidiane C. [UNESP]; Cruz, Nilson C. [UNESP]; Mota, Rogério Pinto [UNESP]; Algatti, Maurício A. [UNESP]; Honda, Roberto Y. [UNESP]; Kuranaga, Carlos [UNESP]; Da Silva, Marcos D. [UNESP] (Springer Nature, 2001)
Thin polymer films were deposited from acetylene and argon mixtures by plasma immersion ion implantation and deposition. The effect of the pulse frequency, v, on molecular structure, optical gap, contact angle and hardness of the films was investigated. It was observed progressive dehydrogenation of the samples and increment in the concentration of unsaturated carbon bonds as the pulse frequency was increased. Film hardness and contact angle increased and optical gap decreased with v. These results are interpreted in terms of the chain unsaturation and crosslinking.
Keywords: Acetylene; Argon; Chemical bonds; Contact angle; Dehydrogenation; Deposition; Hardness; Ion implantation; Molecular structure; Optical properties; Plasma applications; Thin films; Carbon bonds; Optical gap; Plasma immersion ion implantation and deposition; Pulse frequency; Thin polymer films; Organic polymers